The Effects of Social Media Use on Mental Health in Adolescents - Sheng, Yijun (Science Insights Education Frontiers, 2025)
Social media have become an indispensable part of adolescents’ lives because of their vital roles in social interaction and recreation, and their effects on teenagers’ mental well-being have garnered wide attention in academia. This study seeks to investigate the positive and negative effects of social media on adolescent mental health based on the existing literature. Their positive effects include augmenting social support for teenagers’ mental well-being and facilitating their access to mental health knowledge. On the other hand, social media use may impair adolescents’ mental health by deteriorating their psychological states, subjecting them to online bullying, and increasing their exposure to unhealthy content. Also discussed are personal and environmental factors influencing these effects. The article concludes with suggestions on how to mitigate the unfavorable effects of social media on adolescent mental health.